In Search of Graduate Employability: An Exploration of Student Identity - Smith, Sally; Smith, Colin; Taylor-Smith, Ella; Fotheringham, Julia (Asia-pacific journal of cooperative education, 2017)
Universities are adopting institution-wide projects to increase student work placements and work-related learning across all subject disciplines. However, there are large variations between programs in uptake, with limited evidence explaining why this might be the case. This study uses identity theory (Stryker, 1980) to explore student perceptions of placement and work-related learning. Students involved in an institution-wide graduate employability project, including curriculum development with new employability-focused courses, were invited to express their attitudes to work-related learning through in-class surveys. The survey was completed by 103 students across three different programs. Students drew on resources for identity work, including role models and imaginings of themselves in a working environment. However, while they were found to have used developmental networks to support decisions about university courses, many had limited access to networks that could support their career decisions. Finally, the study highlighted that many students lacked awareness of the new courses as opportunities for work-related learning.